WATER AS A SOURCE OF ART CREATION INSPIRATION TABUH KREASI PEPANGGUALAN AMBUH HREDANA BY ANDI PASTIKA PUTRA - I Putu Agus Eko Sattvika (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2022)
The purpose of this study was to examine Tabuh Kreasi Pepanggulan Ambuh Hredana, which was inspired by the Magpag Yeh tradition in the Kapal Village. This research is important to do because water is the source of life in Kapal Village, but it has not been widely used as a source of inspiration in the creation of works of art. The questions are 1. What is the process of creating Tabuh Kreasi Pepanggulan Ambuh Hredana 2. What is the form of Tabuh Kreasi Pepanggulan Ambuh Hredana. This study uses a qualitative method with an ethnomusicological approach. The data sources are from the gending itself, its creator, and cultural figures. Data collection techniques were carried out through participatory observation, interviews, and document studies. The analysis was carried out using the theory of the process of creating works of art based on local wisdom, ethnomusical theory, and functional structural theory. The results of this study are 1. The process of creating Tabuh Kreasi Pepanggulan Ambuh Hredana uses the stages of creation starting from basic capital, creativity, understanding of local culture, concepts, prayers, the process of realizing works of art. 2. Tabuh Kreasi Pepanggulan Ambuh Hredana is in the form of Tabuh Kreasi Pepanggulan with the Triangga concept, with a structure consisting of kawitan, pengawak, and pengecet.